2002
DOI: 10.1210/jcem.87.7.8643
|View full text |Cite
|
Sign up to set email alerts
|

Early Vascular Alterations in Acromegaly

Abstract: Acromegaly is associated with increased cardiovascular mortality; however, little is known about the early atherosclerotic changes occurring in such patients. Endothelial function, in the form of flow-mediated dilation (FMD) of the brachial artery, and intima-media thickness (IMT) of the carotid artery were measured by B-Mode ultrasound in: 1) 18 patients with active acromegaly; 2) 12 subjects cured from acromegaly; 3) 18 subjects without acromegaly, each of them matched to an acromegalic patients for age, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 33 publications
2
61
2
Order By: Relevance
“…A positive association between carotid intima-media thickness (cIMT) and high IGF-I levels has also been observed in acromegalic patients [7]. It has not yet been clarified how the excess of GH/IGF-I induces IMT thickening, but the process could partly be attributed to the direct effects of IGF-I on vascular smooth muscle cells [4]. In our study, macrosomic neonates of diabetic mothers had significantly higher aIMT with lipid alteration.…”
Section: Discussionsupporting
confidence: 54%
“…A positive association between carotid intima-media thickness (cIMT) and high IGF-I levels has also been observed in acromegalic patients [7]. It has not yet been clarified how the excess of GH/IGF-I induces IMT thickening, but the process could partly be attributed to the direct effects of IGF-I on vascular smooth muscle cells [4]. In our study, macrosomic neonates of diabetic mothers had significantly higher aIMT with lipid alteration.…”
Section: Discussionsupporting
confidence: 54%
“…A positive association between cIMT and high IGF-I levels has also been observed in acromegalic patients [6]. It has not been clarified yet how the excess of GH/IGF-I induces IMT thickening, but the process could partly be attributed to the direct effects of IGF-I on vascular smooth muscle cells [4]. Growth hormone hypersecretion as well as GH deficiency are characterized by an increased prevalence of CVD [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension affects at least one third (and possibly up to a half) of all patients with acromegaly and is a key negative prognostic factor for mortality [1,12,13,14]. It is present from the earliest stages and is not necessarily influenced by disease duration [15], although it is more common in older subjects, as in the general population.…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…It is present from the earliest stages and is not necessarily influenced by disease duration [15], although it is more common in older subjects, as in the general population. An elevation in diastolic pressure is usually the first and predominant finding and may be heralded by changes in vascular dynamics [12]. Minimally invasive vascular studies have revealed an increase in arterial pulse wave velocity (a measure of arterial stiffness) and a reduction in flow-mediated dilatation (signifying impaired endothelial function) in newly diagnosed patients [9], which are believed to be mediated, at least in part, by direct effects of GH and IGF-1 on the vascular tree [16].…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
See 1 more Smart Citation